Mobile application for health assessment and intervention - Teh, Malcom Wei Ye (Nanyang Technological University, 2022)
Hyperglycemia, Hypertension, and Hyperlipidemia are widely known as the 3H conditions. Studies have shown that patients who struggle to control these monitorable risk factors, often develop health conditions such as heart disease, diabetes, and stroke. It is thus imperative, to monitor and control these conditions, and provide timely intervention. Akeso is a system designed to provide healthcare professionals, with a convenient method to monitor the 3H conditions of a patient. Using a mobile application built with Unity 3D, the Akeso mobile application comprises two main components: a measurement component and a gamification mechanism in the form of a farming game. The measurement component, collects valuable data on the patient’s health and habits, profiling the patient, and provides intervention in the form of an AI-driven healthcare assistant, which provides lifestyle tips. This data is also made available to healthcare professionals to provide on-hand intervention. The other aspect of the application is a farming game. Its purpose is to gamify healthcare intervention, incentivizing patients to take positive actions in improving their health and lifestyle. Currently, there is a lack of user engagement within the farming game, and thus players may struggle to find a reason to play the farming game. The objective of this project is to improve upon the farming game, with regards to the gameplay experience and game design. The project also introduces new features to the game, in the form of a Job System, to serve as an in-game tutorial and a form of daily player engagement. The research is done to, to ensure the new system, would target key player motivations to promote player engagement. The final features are then integrated into the core Akeso mobile application, where it will then be evaluated through rigorous testing and user surveys.